Kampanye Advertising dalam Era Digital: Pengaruh Media Sosial terhadap Pemaknaan Realitas Sosial - Ridho Hafiz Maulana; Dwi Nur Farah; Hesty Nurlita Fauzia; Much Syahrul Romadhon; M. Nofal Abdillah; Muhammad Ilzam Firdaus (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the transformation of advertising campaigns in the digital era and how social media has an impact on the meaning of consumers' social reality. Through a comprehensive literature review and case analysis, the study identified the mechanisms by which personalized advertising content on social media platforms alters the perception of an individual's social reality. The results showed that the targeting algorithm and filter bubble created a polarized space of information, resulting in a distorted representation of reality. This study contributes to an understanding of how digital advertising strategies affect the social construction of reality and proposes an ethical framework for advertising practitioners in the age of social media.